New Zealand's Muslims and multiculturalism - Kolig, Erich. (Muslim Minorities, 2010)
Issues of integration, multiculturalism and policies of ethnic and religious minority rights have gained greatly in significance in recent years, especially in relation to Muslims. This book deals with the Muslim minority in New Zealand, with special emphasis on policy aspects relevant to the integration of Muslims in the host society. The book also discusses many other issues, among which are Muslim political representation, inner coherence of the Muslim community, effects of public policies, differentiated citizenship, gender issues and gender equality, and points of friction with the encapsulating host society, including the effects of sharia application, radicalism and the fallout of the Danish cartoon affair.